73.7k views
3 votes
Rearrange the equation below to solve for y.
6x+6y= 24

User Rahulsri
by
4.8k points

2 Answers

6 votes

Answer:

y = -x + 4

Explanation:

Step 1: Use the subtraction property of equality

6y = -6x + 24

Step 2: Use the division property of equality

y = -x + 4

User John Yang
by
5.3k points
4 votes

Answer:

y = -x +4

Explanation:

6x+6y= 24

Subtract 6x from each side

6x-6x+6y=-6x+ 24

6y = -6x+24

Divide by 6 on each side

6y/6 = -6x/6 +24/6

y = -x +4

User Ankit Sinha
by
4.5k points